The Human Right to Sexual Autonomy. Issue 5 (August 2021) - Valentiner, Dana-Sophia
Abstract: During the 20 th century, society's view on sexualities has undergone a severe paradigm shift. While moving away from ideas of decency and bawdiness to evaluate legitimate sexuality, concepts of autonomy and consent gained importance. This transformation is also challenging the law. 1 With the broad acceptance of various forms of sexual behavior and sexual orientation, legal regulation based on morality and ethics is outdated. Recent debates on law and sexualities focus on sexual autonomy and its conditions. This is shown especially by the legal debate on sexual violence and criminal law. 2 But the right to sexual autonomy does not only require adequate protection against sexual violence. As a human right, it obliges State Parties to Human Rights Treaties such as the European Convention on Human Rights and the Convention on the Elimination of Discrimination against Women to respect, protect, and fulfill sexual autonomy. This includes the guarantee of freedom from sexual violence, coercion and discrimination, as well as control over one's own body and over the involvement in sexual interactions with others. In order to ensure the different components of sexual autonomy, sexual education and reliable access to information and medical services are necessary. This paper presents an approach concerning the multifaceted dimensions of sexual autonomy through a human rights lens.